Ademetionine in patients with liver disease: a review - Saigal, Sanjiv; Kapoor, Dharmesh; Roy, Dyotona Sen (International Journal of Research in Medical Sciences, 2019)
The aim of the present review is to have an in-depth analysis of the published scientific literature relating to the clinical use of ademetionine in various etiologies of liver disease. Literature search was performed using electronic databases like Pubmed/Medline/others to identify studies on ademetionine in patients with intrahepatic cholestasis, alcoholic liver disease, non-alcoholic fatty liver disease, drug induced liver injury and viral hepatitis. Ademetionine has been studied in various etiologies of liver disease with varying dosing and durations. In patients with chronic and alcoholic liver disease, ademetionine was found to be beneficial in improving liver enzyme levels, increasing glutathione levels, improving signs and symptoms of fatigue, pruritus and jaundice. Positive effects of ademetionine therapy have also been documented in multiple studies in patients with non-alcoholic fatty liver disease, with improvements observed in triglyceride, total cholesterol, alanine transaminase and asprtate transaminase levels and ultrasound grading of fatty change. In patients with drug induced liver injury, improvements were observed in liver biochemical markers and symptoms such as pruritus, fatigue and jaundice. Ademetionine has also been studied in patients with viral hepatitis with improvement in laboratory markers and signs and symptoms. Published data suggest that there is clinical evidence to substantiate the use of ademetionine across indications. Its use has resulted in sustained improvement in biochemical markers; signs and symptoms of liver disease has been observed in both acute and chronic liver disease. Further data is warranted through clinical studies to focus on specific end points of therapy areas, in existing and new indications.